2004
DOI: 10.1081/ias-200033832
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Microsphere‐Based Flow Cytometric Assay for Diagnosis of Celiac Disease

Abstract: The multiplexed particle-based flow cytometric technology proposes a new approach for the diagnosis of autoimmune diseases combining the advantages of conventional methods with the ability to quantitatively determine multiple autoantibodies in the same sample, simultaneously and rapidly. Recently, a commercial kit (FIDIS Celiac, Biomedical Diagnostics, Mane la Vallé, France) was introduced for the simultaneous detection of IgA anti-tissue transglutaminase (anti-tTG), IgG, and IgA anti-gliadin antibodies (AGA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…It is worth mentioning that our cutoff values were substantially higher than those proposed by the manufacturers. More precisely, the cutoff values that we used for ELISA and MFC assay were 25.4 and 69.5 arbitrary units (AU)/ml in controls and 26.2 and 74 AU/ml in hepatitis patients, respectively (49). Specimens with anti-tTG antibody concentrations above these cutoff values by either of the methods used were deemed positive.…”
Section: Methodsmentioning
confidence: 99%
“…It is worth mentioning that our cutoff values were substantially higher than those proposed by the manufacturers. More precisely, the cutoff values that we used for ELISA and MFC assay were 25.4 and 69.5 arbitrary units (AU)/ml in controls and 26.2 and 74 AU/ml in hepatitis patients, respectively (49). Specimens with anti-tTG antibody concentrations above these cutoff values by either of the methods used were deemed positive.…”
Section: Methodsmentioning
confidence: 99%
“…Although sensitivity estimates differ across studies in terms of absolute values, the studies do not show significant heterogeneity in terms of diagnostic power. The SROC curve analysis showed that the diagnostic performance of the various studies closely follows a satisfactory defined path of trade-off between sensitivity and specificity (7,16,21,28,33,37). The independent estimates of sensitivity and specificity can be reliable estimates (perhaps not for the rh-tTG studies using the most popular assay), since they are relatively close to the SROC curve.…”
Section: Discussionmentioning
confidence: 99%
“…A FIDIS kit has been reported for this determination. 89 Twenty-one samples from patients with untreated, biopsy confirmed celiac disease were tested, as well as sera from 207 blood donors and 181 patients with chronic hepatitis. The results for the celiac markers showed good agreement with ELISA; the multiplexed assay generated fewer positive results for the hepatitis controls.…”
Section: Other Applications Of Multiplex Methods To Autoantibodiesmentioning
confidence: 99%